Socioeconomic Development Sustainability Analysis: A Review Of Corporate CSR And ESG In Indonesia - Ahmad Thoriq Alfan; Nurlaila Harahap; Muhammad ikhsan Harahap (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research elaborates the influence of ESG and CSR on socio-economic development in Indonesia. With a sample of 11 companies and crosschecking statements according to GRI g4. This research aims to provide awareness to each company about the impacts it will face in a sustainable and advanced social economy. The analytical method used is multiple regression analysis using the CEM (Common Effect Models) model. The results of the research show that the calculated F value is 454.2893 > F table which is 3.327654 and the sig value is 0.00000 < 0.05, so this means that H0 is rejected and Ha is accepted, so this means that the CSR variable and ESG have a very significant effect on socio-economic development, so ESG and CSR disclosures have a significant effect on Socio-Economic Development in Indonesia.